2018
DOI: 10.1186/s42155-018-0031-3
|View full text |Cite
|
Sign up to set email alerts
|

Trans-arterial embolisation (TAE) in haemorrhagic pelvic injury: review of management and mid-term outcome of a major trauma centre

Abstract: BackgroundManagement of pelvic fracture associated haemorrhage is often complex with high morbidity and mortality rates. Different treatment options are used to control bleeding with an on-going discussion in the trauma community regarding the best management algorithm.Main bodyRecent studies have shown trans-arterial embolisation (TAE) to be a safe and effective technique to control pelvic fracture associated haemorrhage. Computed tomography (CT) evidence of active bleeding, haemodynamic instability, and pelv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 60 publications
(93 reference statements)
1
15
0
1
Order By: Relevance
“…Since the 1970s, the use of TAE in pelvic fractures has continued to increase with reported success rates between 80% and 100% depending on the definition of "success". 12,[16][17][18] In our study, patients who underwent angiography were found to be significantly older and were more likely to be male versus those who did not have angiography. No significant difference was found between mortality, ICU LOS, or hospital LOS in these 2 cohorts.…”
Section: Discussionmentioning
confidence: 52%
“…Since the 1970s, the use of TAE in pelvic fractures has continued to increase with reported success rates between 80% and 100% depending on the definition of "success". 12,[16][17][18] In our study, patients who underwent angiography were found to be significantly older and were more likely to be male versus those who did not have angiography. No significant difference was found between mortality, ICU LOS, or hospital LOS in these 2 cohorts.…”
Section: Discussionmentioning
confidence: 52%
“…According to the Eastern Association for Surgery of Trauma guidelines, when the cause of bleeding is intra-abdominal haemorrhage or intra-abdominal organ damage, TAE is a treatment option as long as the patient's vital signs are stable [4]. Furthermore, when the cause of bleeding is retroperitoneal haemorrhage such as from pelvic fracture, TAE is the rst choice for bleeding control, even if the patient's vital signs are unstable [16]. Kuo et al reported that in trauma with haemorrhagic shock, there were cases requiring TAE among those who did not initially show extravasation on CE-CT scanning.…”
Section: Discussionmentioning
confidence: 99%
“…The other patient had angiography performed at a time interval of more than 5 h after a negative CT, due to increasing hemodynamic instability. Such discrepancy between extravasation seen on CT and angiography can be related to vessel spasm after secondary local inflammatory response in patients with bleeding or hypotension [ 37 , 43 ]. According to Dreizin et al, arterial bleeding can be occult at CT in 20–40% of patients [ 41 , 44 ].…”
Section: Discussionmentioning
confidence: 99%